GLOBALIZING HOMBO BATU THE ROLE OF ENGLISH IN PROMOTING NIAS LOCAL WISDOM ON THE INTERNATIONAL STAGE - Harefa, Darmawan (Universitas Nias Raya, 2025)
This study aims to examine the role of the English language in promoting the local wisdom of Nias, specifically the Hombo Batu tradition, to the international stage. Hombo Batu, which symbolizes bravery and physical strength in Nias society, has the potential to become a globally recognized cultural attraction. English, as a global lingua franca, plays a crucial role in bridging the gap between local culture and international audiences. Through social media, international festivals, and tourism websites, English is used to introduce the meaning and values embedded in Hombo Batu. This study employs a descriptive qualitative method, with data collection techniques including literature review, digital media observation, and semi-structured interviews with cultural practitioners, academics, and tourism managers. The findings of this study show that, while the use of English is highly effective, challenges in maintaining cultural integrity remain. The research concludes that, despite the effectiveness of English in introducing Hombo Batu, there is a need for enhanced translation quality and collaboration between cultural experts and communication professionals to ensure that traditional values are preserved when presented to the international audience. Additionally, empowering the younger generation of Nias to promote their culture is essential.